2014
DOI: 10.1158/1541-7786.mcr-13-0489
|View full text |Cite
|
Sign up to set email alerts
|

P-Cadherin Promotes Ovarian Cancer Dissemination Through Tumor Cell Aggregation and Tumor–Peritoneum Interactions

Abstract: More than 60% of patients who are diagnosed with epithelial ovarian cancer (EOC) present with extensive peritoneal carcinomatosis. EOC cells typically disseminate by shedding into the peritoneal fluid where they survive as multi-cellular aggregates and then implant onto peritoneal surfaces. However, the mechanism that facilitates aggregation and implantation of EOC cells is poorly understood. The cell adhesion molecule P-cadherin (CDH3) has been reported to be induced during early progression of EOC and to pro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
41
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 39 publications
(71 reference statements)
1
41
0
Order By: Relevance
“…This suggests that other proteins may also be involved. Other cadherins, such as Nand P-cadherin and other desmosomal adhesion proteins (such as DSG1, DSG3, DSG4, DSC1 and DSC3), might take part in this process as their activities are associated with cancer development (1,6,22,30,40). Their involvement requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that other proteins may also be involved. Other cadherins, such as Nand P-cadherin and other desmosomal adhesion proteins (such as DSG1, DSG3, DSG4, DSC1 and DSC3), might take part in this process as their activities are associated with cancer development (1,6,22,30,40). Their involvement requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Metastatic dissemination is associated with deregulation of numerous cell processes, including the ability of tumor cells to aggregate (1). Both proand anti-aggregation forces contribute to promoting cancer dissemination: loss of cohesion forces in the primary tumor allows individual cancer cells or small groups of cells to escape into the lymphatic and circulatory systems (2), whereas the increased cellcell adhesiveness of metastatic cells allows them to form multicellular homotypic aggregates, which have an increased chance of survival once detached from the primary tumor (3).…”
Section: Introductionmentioning
confidence: 99%
“…CS is a hallmark of EMT [75], the process by which epithelial cells lose their characteristic polarity, disassemble cell junctions, and become more migratory as a precursor to invasion and metastasis (they acquire properties analogous to mesenchymal cells) [19,24,60,[76][77][78][79][80][81]. In this setting, CS typically describes a process where the normal expression of E-cadherin is replaced by the abnormal expression of N-cadherin, or where N-cadherin expression is increased and E-cadherin levels remain unchanged [19,60,75].…”
Section: Cadherin Switchingmentioning
confidence: 99%
“…Numerous studies have highlighted the ability of spheroids to acquire chemoresistant, and stem-like properties, both of which have major implications for disease outcome (6,11). Thus far, it is believed that interactions between various cell adhesion molecules and extracellular matrix components contribute to the formation of MCAs, including integrins, fibronectin, and cadherins (5,7,8,12). Interestingly, studies have also shown that gene and protein expression can differ between cancer cells grown in monolayers versus those within multicellular aggregates (11,13).…”
mentioning
confidence: 99%